MOBILISASI DINI TERHADAP PEMULIHAN PERISTALTIK USUS DAN SKALA NYERI PASIEN POST PEMBEDAHAN - Arianti, Arianti; Mayna, Nadila Putri; Hidayat, Yuda (Universitas Muhammadiyah Magelang, 2020)
Postoperative complications such as pain, malnutrition, delayed wound healing and ileus were frequently found and become a challenge for health workers. Early mobilization is recognized as an approach that may help in preventing as well as decreasing the further effect of those complications. However, the implementation of early mobilization in hospitals were still limited to verbal commands without providing direct assistance to postoperative patients. Therefore, this study tries to give evidence-based nursing in PKU Muhammadiyah Gamping Hospital in improving nursing care to postoperative patient outcomes by giving early mobilization. The purpose of this study was to find the effect of early mobilization on the recovery time of intestinal peristalsis and pain scale in post-operative patients. This research was pre-experimental research using a static group comparison research design with a cross-sectional approach. The sampling technique used purposive sampling with specific criteria who was in adult age and received regional anesthesia. This study found 40 subjects consisting of 20 subjects in the intervention group and 20 subjects in the control group. The Mann-Whitney statistical test proved a significant effect on early mobilization on intestinal peristalsis recovery (p = 0.000) Gand pain scale (p = 0.001).